Those in Peril - Smith, Wilbur A. (London Macmillan, 2011)
Hazel Bannock is heir to the Bannock Oil Corporation, one of the major global oil producers. While cruising the Indian Ocean, her yacht is hijacked by Somalian pirates and her nineteen-year-old daughter, Cayla, kidnapped. The pirates demand a crippling twenty-billion-dollar ransom for her release, and complicated political and diplomatic sensitivities render the major powers incapable of intervening. With growing evidence of the horrific torture to which Cayla is being subjected, Hazel calls on Hector Cross to help her rescue her daughter. Hector is the man behind Cross Bow Security, the company contracted to Bannock Oil Corporation to provide all their protection. He is a formidable fighting man. Between them, Hazel and Hector are determined to take the law into their own hands.
Keywords: Hijacking of Ships -- International Relations -- Oil Industries